Understanding quality-of-life determinants in coronary arterial disease patients - Muliantino, Mulyanti Roberto; Ananda, Yuanita; Mailani, Fitri; Sarfika, Rika; Safitri, Dea Anggun; Aulia, Nurul (Intelektual Pustaka Media Utama, 2024)
The study aimed to examine the correlation of determinant factors of quality of life in coronary arterial disease (CAD) patients, including knowledge of disease, smoking cessation, physical activity, and dietary regulation. A quantitative, cross-sectional study using convenience was conducted among 216 CAD patients from the West Sumatra, Indonesia, outpatient cardiovascular center. Data were collected using the cardiovascular disease knowledge assessment questionnaire, smoking cessation, physical activity, diet questionnaire, and self-assessment questionnaire to measure knowledge of the disease, smoking cessation, physical activity, diet, and quality of life, respectively data analysis using Chi-square, Pearson correlation, and multivariate linear regression test. The result showed that dietary regulation was the most influential variable on the quality of life of CAD patients (B=1.670, SE=0.341), followed by smoking cessation, physical activity, and knowledge about the disease. Our data suggest that dietary regulation, smoking cessation, and regular physical activity as modifiable CAD risk factors and disease knowledge improve the quality of life of CAD patients. Future research and clinician intervention for CAD awareness of lifestyle modification should be expanded to focus on barriers and their challenges during cardiac rehabilitation.